Pengembangan Umkm Sandalku Handmade Kedung Baruk Melalui Branding Di Media Sosial Instagram - Riva Dika Adhilni; Maharani Ikaningtyas (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Branding is the process of creating, building, and maintaining an image or identity for a product, service, organization, or even individual consumers. The main purpose of branding is to differentiate an entity from its competitors and create a unique and memorable positive perception among consumers. One of the benefits that will be obtained is to increase sales and image of MSMEs. The method used is a qualitative method by (1) conducting interviews and discussions (2) conducting mentoring and training (3) conducting monitoring related to mentoring. As a result of this activity, Sandalku Handmade MSMEs can successfully create a strong brand identity and distinguish themselves from their competitors. Through this branding activity, Sandalku Handmade SMEs are expected to be able to utilize social media platforms to build brand image and succeed in an increasingly competitive market.